Pengaruh Kebijakan Kompensasi Terhadap Semangat Kerja Karyawan PT. Intika Delta Borneo (IDB) - Eka Wira Putra; Devi Yasmin; Fenni Supriadi (Universitas Muhammadiyah Pontianak, 2018)
This research aims to determine the effect of compensation policy on spirit at work of employees in PT. Intika Delta Borneo (IDB). The type of this study is using the descriptive method, the technique of collecting a sample in this study is the purposive sampling method. Based on the selected criteria, there are 44 respondents. The data analysis technique of this study is a simple linear regression, correlation coefficient (R), determination coefficient (R2), model feasibility analysis (Test F). The results of this study are known that the regression equation Y = 3.232 + 0.233 (X). Correlation coefficient value (R) is 0.446, which means that the relationship between Compensation Policy and Spirit at work of Employees at PT. Intika Delta Borneo is medium. The coefficient of determination (R2) value is 0.199. It means that the contribution of the Compensation Policy variable in influencing the increase and the decrease of the Employee Spirit in PT. Intika Delta Borneo is 19.9%, and the remaining 80.1% is affected by other variables not examined in this research. The calculated F value is 10.413. It is higher than F table that has 4.07. It means that the linear regression model can determine the amount of employee spirit which is influenced by the compensation policy of PT. Intika Delta Borneo.